If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(-0.6666666667 + -1.333333333y) + -4y = 2 (-0.6666666667 * -3 + -1.333333333y * -3) + -4y = 2 (2 + 3.999999999y) + -4y = 2 Combine like terms: 3.999999999y + -4y = -0.000000001y 2 + -0.000000001y = 2 Add '-2' to each side of the equation. 2 + -2 + -0.000000001y = 2 + -2 Combine like terms: 2 + -2 = 0 0 + -0.000000001y = 2 + -2 -0.000000001y = 2 + -2 Combine like terms: 2 + -2 = 0 -0.000000001y = 0 Solving -0.000000001y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-0.000000001'. y = 0 Simplifying y = 0
| x^6+19x^3-216=0 | | 9x+7(-3x-5)=-43-4x | | 8y+6x=-4 | | (x+1)(3x^2-12)=0 | | -3x-4(-0.5+-0.75x)=2 | | y-12=7 | | 5x^2-19x+18= | | 2x+5(2-1x)=10 | | 7(3w+1)-9(1+2w)=-2(w+4)-(4w-5)+6 | | 1=x+.333x | | -9a^2-5a^2=0 | | y=2-5+-2.5y | | x+2(1.5)=4 | | 9(4-2y)-4y=3 | | -5s=24 | | -3p=72 | | y^2-3y+9=0 | | -2(-0.5-2y)-4y=1 | | 6v^2-3v-15=-2v | | 5.1(x-2)=1.02 | | 12y+6x=-3 | | x=-0.5+-2y | | -2-4y=1 | | 4.75=a+3.6/2 | | X-25=17 | | 3x^2+14=0 | | y^2-2y^2+6y-12=0 | | 16Y^2=9 | | 21=a+28/2 | | 7x^2=-6x | | 4-(2z-7)=5(2z+3) | | X-31=10 |